ANALISIS HAMBATAN LITERASI MEMBACA PERMULAAN PADA SISWA KELAS I SEKOLAH DASAR: STUDI KASUS DI SDN NGEMPLAK KIDUL 02 - Nila Purnaningtyas; Triningsih; Puji Yatmoko; Dwi Ari Novianto; Agung Slamet Kusmanto (STKIP Subang, 2026)
Reading literacy is a fundamental skill that elementary school students must acquire to support overall learning success. However, in reality, early-grade students still experience significant difficulties in early reading development. This study aimed to identify the forms of early reading literacy difficulties and their contributing factors among first-grade students at SDN Ngemplak Kidul 02. The study employed a qualitative approach using a case study method. Data were collected through observations, reading ability tests, and interviews with teachers and parents. The findings revealed that the students experienced difficulties in recognizing letters, distinguishing visually similar letters, associating letters with their corresponding sounds, blending syllables into meaningful words, and reading simple words and sentences fluently. These difficulties were influenced by internal factors, including weaknesses in visual perception, phonological processing difficulties, low learning motivation, and a lack of self-confidence. External factors included limited reading habits at home, inadequate access to reading materials, and insufficient support from parents and teachers. The findings highlight that synergistic collaboration between schools and families is essential to support the optimal development of students' reading literacy skills.